Effects of guanidinoacetic acid on in vitro rumen fermentation and microflora structure and predicted gene function - Dong, Chenyang; Wei, Manlin; Ju, Ji; Du, Liu; Zhang, Runze; Xiao, Ming; Zheng, Yongjie; Bao, Hailin; Bao, Meili (Frontiers in Microbiology, 2024)
The fermentation substrate was supplemented with 0% guanidinoacetic acid (GAA) (control group, CON), 0.2% GAA (GAA02), 0.4% GAA (GAA04), 0.6% GAA (GAA06) and 0.8% GAA (GAA08) for 48 h of in vitro fermentation. Gas production was recorded at 2, 4, 6, 8, 12, 24, 36 and 48 hours of fermentation. The gas was collected, and the proportions (%, v/v) of H2, CH4 and CO2 were determined. The rumen fermentation parameters, including pH, ammonia nitrogen (NH3-N), microbial protein (MCP) and volatile fatty acids (VFAs), were also determined. Furthermore, the bacterial community structure was analysed through 16S rRNA high-throughput sequencing. The gene functions were predicted using PICRUSt1 according to the Kyoto Encyclopedia of Genes and Genomes (KEGG). The results showed that with the increase in GAA supplementation levels, the MCP and the concentration of rumen propionate were significantly increased, while the concentration of isovalerate was significantly decreased (P<0.05). The results of microbial diversity and composition showed that the Shannon index was significantly decreased by supplementation with GAA at different levels (P<0.05), but the relative abundance of norank_f_F082 and Papillibacter in the GAA06 group was significantly increased (P<0.05). Especially in group GAA08, the relative abundances of Bacteroidota, Prevotella and Prevotellaceae_UCG-001 were significantly increased (P<0.05). The results of gene function prediction showed that the relative abundances of the functions of flagellar assembly, bacterial chemotaxis, plant‒pathogen interaction, mismatch repair and nucleotide excision repair were significantly decreased (P<0.05), but the relative abundances of bile secretion and protein digestion and absorption were significantly increased (P<0.05). In conclusion, supplementation with 0.8% GAA enhanced in vitro rumen fermentation parameters, increased the relative abundance of Prevotella and Prevotellaceae_UCG-001 in the rumen, and increased the metabolic pathways of bile secretion and protein digestion and absorption.